2017
DOI: 10.5505/tjtes.2017.95079
|View full text |Cite
|
Sign up to set email alerts
|

Is Nighttime Laparoscopic General Surgery Under General Anesthesia Safe?

Abstract: BACKGROUND: Fatigue and sleep deprivation can affect rational decision-making and motor skills, which can decrease medical performance and quality of patient care. The aim of the present study was to investigate the association between times of the day when laparoscopic general surgery under general anesthesia was performed and their adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…Night-time surgery has often been associated to a higher morbidity or mortality rate, previous studies confirming these hypotheses. 1,2 However, the primary outcome of our study confirmed the results of several other studies that contradicted the correlation between night-time surgery and worse clinical outcomes, such as postoperative complications or graft failure. Kienzl-Wagner et al 12 showed no differences in postoperative complications, and even less acute rejection (22.6% vs. 18.3% in night-time graft recipients, p = .15) for night-time KT.…”
Section: Discussionsupporting
confidence: 88%
“…Night-time surgery has often been associated to a higher morbidity or mortality rate, previous studies confirming these hypotheses. 1,2 However, the primary outcome of our study confirmed the results of several other studies that contradicted the correlation between night-time surgery and worse clinical outcomes, such as postoperative complications or graft failure. Kienzl-Wagner et al 12 showed no differences in postoperative complications, and even less acute rejection (22.6% vs. 18.3% in night-time graft recipients, p = .15) for night-time KT.…”
Section: Discussionsupporting
confidence: 88%
“…Multiple stud ies have examined the impact of afterhours operating on appendectomy and cholecystectomy outcomes, with mixed results. [13][14][15][16][17][18] Delay to operative intervention has been difficult to study because of the diversity of disease processes, severity of presentation and variable comorbidities in EGS patients.…”
mentioning
confidence: 99%
“…Recent evidence has shown that night-time surgery is associated with increased risk of intraoperative complication. 11,12 The improvement in these efficiency outcomes can be attributed to the streamlined work processes and improved communication between disciplines. Most studies on acute care surgeries also reported similar benefits.…”
Section: Discussionmentioning
confidence: 99%
“…With a greater proportion of daytime surgeries, the presumption is that there could be fewer mistakes as staff are more alert and vigilant. Recent evidence has shown that night‐time surgery is associated with increased risk of intraoperative complication 11,12 …”
Section: Discussionmentioning
confidence: 99%